Penelusuran sisa-sisa Kerajaan yang hilang dibalik Letusan Gunung Tambora di Situs Doro Bente - Yuda Haribuana, I Putu; Indria, Ida Ayu Gede Megasuari; Sumerata, I Wayan; Keling, Gendro (PURBAWIDYA, 2024)
The archaeological research in the Tambora Peninsula was initiated by the National Archaeological Research Center in 2006, and from 2008 onwards, it was continued by the Archaeological Office in Denpasar-Bali until 2021. Numerous archaeological pieces of evidence have been successfully excavated from Mount Tambora's pyroclastic material. Recent research has been focused on the Doro Bente Site on the Teluk Saleh Peninsula. The research aims to understand the sequence of historical events on settlement centers based on artifact evidence resulting from the eruption of Mount Tambora in 1815. The study employs qualitative, descriptive methods, and a geoarchaeological approach. Data acquisition involves excavation, surveys, and literature studies. Stratigraphic analysis is conducted to identify sediment matrices and understand the deposition sequence. Excavation activities have uncovered significant artifacts such as ceramic fragments, pottery, animal bones, and shell fragments. Micro-scale deposition chronology in excavation box B28U18 indicates that the three lower layers, the oldest, were deposited in a marine environment, followed by five layers of pyroclastic material from the 1815 eruption of Mount Tambora. The geographical factors and available natural resources make Sumbawa Island a focal point for Chinese and European attention from the 13th to the 19th centuries AD.